The Code of the City of Atlanta 164 (William T. Newman ed., 1879) - (:unkn) unknown (My University, 1879)
Ch. 42-Powder, § 460: Prohibited the sale of gunpowder without obtaining a license from the clerk of the council. The license would expire after one year. Violators fined one hundred dollars and costs of trial for each and every day the party violated the ordinance, or imprisoned not more than thirty days in the station house or common jail of Fulton County.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER